A repair material and preparation method thereof

By using the core-shell structure of nanofibers in the skin wound repair material, using autogenous platelet-rich plasma as the growth factor release source in the core layer, combined with the shell composed of modified polycaprolactone and ε-polylysine, the problem that active substances in the prior art are difficult to maintain high concentrations and exogenous active substances may cause allergic reactions, and efficient wound repair and wound repair efficiency are achieved.

CN116370692BActive Publication Date: 2025-04-15QINGDAO ZHONGKE KAIER TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310400936.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-14
Publication Date
2025-04-15
Estimated Expiration
2043-04-14

AI Technical Summary

Technical Problem

In the prior art nanofiber dressings used for skin wound repair, the arrangement of the dressing directly contacts the wound based on active substances or drug ingredients can easily lead to the active substances or drug ingredients being affected by the wound microenvironment and it is difficult to maintain a higher concentration that promotes repair and growth; the dressing uses a core-shell structure to place exogenous active substances or drug ingredients in the inner layer, and the exogenous active substances cannot overcome the body allergic reactions that may occur during use, and the single-set shell structure cannot adjust the release strategy and release rate of the active substances or drug ingredients to ensure the applicability and targeting of the induction of wound repair activity and efficiency improvement.

Method used

A core-shell structure repair material based on nanofibers is used, where the core layer of the nanofiber contains autogenous platelet-rich plasma for releasing growth factors, the shell consists of polycaprolactone and ε-polylysine, the fiber pore size of the shell is smaller than that of bacteria, allowing growth factors to pass through and accumulate on the wound surface, and the modified components of the shell improve the wetting and antibacterial properties of the fibers.

Benefits of technology

It significantly improves the ability and repair efficiency of wound repair, ensures that the wound surface environment can maintain a high concentration of growth factors, avoids allergic reactions in the body, and improves the activity induction and efficiency of wound repair by adjusting the release strategy and rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116370692B_ABST
    Figure CN116370692B_ABST
Patent Text Reader

Abstract

The present invention relates to a repair material and a preparation method thereof, and belongs to the technical field of medical materials. The repair material comprises: a core layer at least for providing growth factors; a shell layer at least allowing the growth factors of the core layer to pass through and be released; wherein the repair material is configured as a nanofiber having a core-shell structure based on the core layer and the shell layer in a manner that at least includes a coaxial arrangement. The repair material of the present application can overcome the problem that the active substances or drug components of the dressings in the prior art are affected by the wound microenvironment and are difficult to maintain a high concentration that promotes repair growth based on the nanofiber material arranged in the shell layer and the active substance arranged in the core layer, and exhibit excellent antibacterial and tissue regeneration promoting properties. The selection of active substances can overcome the problem that exogenous substances are prone to allergic reactions, and based on the distribution of the concentration content of the active substance growth factor, the induction effect on the activity of wound tissue cells and the healing and repair efficiency can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical materials, in particular to a repair material and a preparation method thereof. Background Art

[0002] The skin covers the whole body and becomes an important barrier to protect the internal structure of the human body and maintain the internal environment. However, the skin is susceptible to trauma. At present, skin trauma is mainly divided into acute trauma and burns. When the wound heals naturally without intervention, scars are often left, which leaves a huge psychological barrier for the patient. At this stage, the basis for treating trauma is mainly: inhibiting the reproduction of wound bacteria to reduce infection, increasing the concentration of active substances to accelerate wound healing, and inhibiting scars or relieving patient pain based on the structure and composition of dressings. For example, for skin burns, gauze and ointments for treating burns are generally used, but the porosity of gauze is too high, the pore size is too large, and the skin has poor adhesion, which is not conducive to preventing the invasion of external bacteria. In addition, its high absorption capacity will cause wound dehydration and rough bacterial growth, and secondary damage may also be caused when the gauze is removed. The pore size of nanofiber membrane is smaller than that of bacteria, and it has a similar structure to the extracellular matrix, which is a good substitute for gauze. Among them, electrospun nanofiber membrane has broad prospects in the application field of wound dressings due to its intrinsic properties such as high specific surface area, high porosity and similar structure to the skin extracellular matrix. Ointment is an exogenous drug with a relatively simple ingredient, and the therapeutic effect varies from person to person.

[0003] Various new wound dressings have been developed in the prior art, such as films, hydrocolloids, hydrogels and micro / nanofibers. Nanofiber materials include chitosan, polycaprolactone (PCL), polylactic acid (PLA), etc. In order to enhance the ability of dressings to prevent bacterial infection and promote wound healing, growth factors with antibacterial effects are often loaded into dressing nanofibers. For example, ε-polylysine ε-PL (Epsilon Polylysine) is a nutrient necessary for tissue repair. ε-PL incorporated into nanofibers can improve the fiber's wettability and exhibit good antibacterial properties. Autologous platelet-rich plasma, or PRP (Platelet Rich Plasma), not only contains rich growth factors that can promote angiogenesis and cell proliferation, but also because it is autologous, the proportion of each growth factor in PRP varies slightly from person to person, which can achieve personalized treatment and avoid allergic reactions in the body. However, when PRP is directly applied to the affected area, it releases growth factors after being activated. However, since the growth factors are quickly decomposed by enzymes in the wound microenvironment, it is difficult to maintain a high concentration. Encapsulating PRP into nanofibers can avoid this disadvantage. Considering that PRP is water-soluble and most biodegradable materials are hydrophobic materials, forming core-shell structure fibers with PRP and fibers can avoid the problem of solvent miscibility during spinning.

[0004] Among the existing technical solutions for wound repair materials and methods, for example, the patent with publication number CN110101897A discloses a method for in-situ care of burn and scald skin, including preparing a burn and scald care spinning solution, spinning the burn and scald care spinning solution using an in-situ electrospinning device, controlling the distance between the nozzle and the receiving wound, and depositing a nanofiber antibacterial dressing in-situ on the burn and scald affected area to achieve in-situ care of burns and scalds. This technical solution is based on the electrospinning equipment to deposit the nanofiber antibacterial dressing in-situ on the burn and scald wound, but the antibacterial dressing will not contact the wound, resulting in a gap or interval between the wound surface and the dressing, and the nanofiber antibacterial dressing cannot effectively deliver the active ingredients of the drug to the wound surface.

[0005] The patent with the announcement number CN107137748B discloses a core-shell electrospun chitosan nanofiber wound dressing and its preparation method, wherein the nanofiber of the dressing used for the repair of the affected part is configured as a core-shell structure, chitosan, sodium carboxymethyl cellulose, and polyethylene oxide are added to an aqueous solution containing a small amount of acetic acid and ethanol to obtain an outer layer solution, polyethylene oxide is added to the aqueous solution to obtain solution A, and a lithium ion solution is prepared, and a small amount of sodium pyrophosphate is added to obtain solution B, and solution A and solution B are mixed to obtain an inner layer solution, and the outer and inner layer solutions are prepared into a core-shell nanofiber dressing by coaxial electrospinning. The patent with the publication number CN110464866A discloses a core-shell drug-loaded nanofiber dressing and its preparation method, wherein the nanofiber of the dressing also adopts a core-shell structure, the core layer is composed of honey and polyvinyl alcohol, and the shell layer is composed of ε-polylysine and polycaprolactone. The above technical solution prepares a core-shell structure based on electrospinning technology and places different substances of the nanofiber dressing in the core layer and the shell layer, so that the shell layer is prepared from a hydrophobic polymer with suitable mechanical properties and biocompatibility and a performance-improving component, while the core layer is prepared from materials or active substances that control the physical and chemical properties of the nanofibers. However, the active substances are exogenous ingredients and cannot overcome the allergic reactions of the body that may occur during use, and may cause negative effects based on the patient's own specific conditions; and the exogenous active substances placed in the core layer cannot be specifically set according to the differences in the internal environment of the human body, resulting in the exogenous active substances being unable to guarantee the activity induction and efficiency improvement effects on wound repair.

[0006] The patent with publication number CN108434529A discloses an in-situ autologous bionic repair material for fat liquefaction wounds, and its preparation method and application. The in-situ autologous bionic repair material for fat liquefaction wounds includes an autologous functional layer, a biological functional layer and a surface isolation layer; wherein the autologous functional layer is PRP prepared after collecting whole blood from patients; the biological functional layer is one or more of chitosan fiber, alginate fiber, collagen fiber, oxidized cellulose fiber, gelatin fiber, etc., which is a fiber layer structure, and its 3D mesh structure can be used for the components in the autologous functional layer to infiltrate and fix; the surface isolation layer is a polyurethane semipermeable membrane. However, the autologous functional layer directly set on the wound will cause the autologous platelet-rich plasma to directly contact the wound microenvironment and be activated, thereby releasing active sites that promote repair growth, but the active substances will be quickly decomposed by the enzymes in the wound microenvironment, and it is difficult to maintain a high concentration continuously.

[0007] Based on the above analysis, in the nanofiber dressings used for skin wound repair in the prior art, the arrangement of the dressings based on the direct contact of the active substances or drug ingredients with the wound surface easily causes the active substances or drug ingredients to be affected by the wound surface microenvironment and it is difficult to maintain a high concentration that promotes repair growth; the dressings place exogenous active substances or drug ingredients in the inner layer based on the core-shell structure, and the exogenous active substances cannot overcome the allergic reactions of the body that may occur during use, and the single shell structure cannot adjust the release strategy and release rate of the active substances or drug ingredients to ensure the applicability and pertinence for the induction of activity and improvement of efficiency of wound repair.

[0008] In addition, on the one hand, there are differences in understanding among those skilled in the art; on the other hand, the inventor studied a large number of documents and patents when making the present invention, but due to space limitations, not all details and contents are listed in detail. However, this does not mean that the present invention does not have the characteristics of these prior arts. On the contrary, the present invention already has all the characteristics of the prior art, and the applicant reserves the right to add relevant prior art to the background technology. Summary of the invention

[0009] In view of at least some of the shortcomings of the prior art, the present invention provides a repair material, comprising: a core layer for providing at least growth factors, and a shell layer for allowing at least the growth factors in the core layer to pass through and be released, wherein the repair material is configured as a nanofiber having a core-shell structure based on the core layer and the shell layer in a manner that at least includes a coaxial arrangement. The shell layer includes at least a first component for forming the main body of the shell layer and a second component for modifying the first component; the core layer includes at least a third component for releasing growth factors. The first component can be configured as polycaprolactone, the second component can be configured as ε-polylysine, and the third component can be configured as autologous platelet-rich plasma.

[0010] The degradable organic polymers such as polycaprolactone used in this application are used as the main spinning material to control the fiber morphology and ensure the fiber structure. Compared with the existing repair dressings or gels, it can form an effective barrier to protect the tissue wound surface, and ensure that the active ingredients of the drug are not affected and their release can be controlled. Polycaprolactone also has excellent biological properties and filament properties, and the material is non-toxic, harmless and non-irritating. The added ε-polylysine is used to adjust the wettability and antibacterial properties of polycaprolactone, which makes up for the strong hydrophobic properties of polycaprolactone, so that the electrospun nanofiber membrane can absorb excess tissue exudate from the affected area, ensure a relatively moist environment of the affected area, and significantly enhance the adhesion of the repair material to the tissue cells.

[0011] In view of the problem that the arrangement of dressings in the prior art based on the direct contact of active substances or drug ingredients with the wound surface easily causes the active substances or drug ingredients to be affected by the wound surface microenvironment and it is difficult to maintain a high concentration that promotes repair and growth. The repair material suitable for wounds in this application is a nanofiber with a core-shell structure. The nanofiber has functional materials corresponding to the core layer and the shell layer based on the core-shell structure, so that the repair material of this application can significantly improve the repair ability and repair efficiency for wounds. Specifically, the prior art proposes a variety of polymer nanofiber materials to replace traditional gauze for dressings suitable for wounds. In order to improve the repair efficiency of nanofiber materials, nanofiber materials are often used in combination with active substances that can release growth factors. However, when the active substances are in direct contact with the microenvironment on the wound surface, the active substances or growth factors will be decomposed by the wound enzymes and cannot maintain a high concentration that promotes wound recovery. The repair material of the present application can place the active substance used to provide growth factors in the core layer based on the core-shell structure of the nanofiber, and arrange the nanofiber material used as the main body of the material in the shell layer. The fiber pore size of the shell layer is smaller than that of the bacteria, which can effectively isolate the external environment of the wound and prevent bacterial invasion. The fiber pore size of the shell layer can allow the growth factors continuously released by the core layer to pass through and accumulate on the wound surface, so that the wound surface environment can maintain a higher concentration of growth factors to ensure the induction efficiency of wound repair.

[0012] To solve the problem that exogenous active substances cannot overcome the allergic reaction of the body that may occur during use and to improve the applicability of the repair material for wound repair. The repair material of the present application adds a second component for improving the physical properties to the first component as the main body of the nanofiber shell, so that the shell of the nanofiber can obtain physical properties that are more suitable for wound repair based on the second component, and the physical properties may include antibacterial property, hydrophilicity, fiber pore size, fiber strength, etc. For example, the first component and the second component are respectively configured as polycaprolactone and ε-polylysine, and ε-polylysine can effectively improve the wettability and antibacterial property of polycaprolactone, thereby ensuring that the shell including polycaprolactone and ε-polylysine can facilitate the attachment and infiltration of cells, is conducive to cell adhesion and proliferation, and has good biocompatibility. The active substance used to release growth factors in the present application can be autologous PRP, which not only contains rich growth factors, can promote angiogenesis and cell proliferation, but also because it is autologous, the component ratio of each growth factor of PRP is slightly different from person to person, which can achieve individualized treatment and avoid allergic reactions of the body. Considering that self-derived PRP is water-soluble and most biodegradable materials are hydrophobic, making nanofibers into core-shell structures can also avoid the problem of solvent miscibility during spinning.

[0013] Moreover, the repair material of the present application can also control the speed of the core layer releasing growth factors to the wound surface and the effect of the shell layer on the wound surface based on the adjustment of the preparation parameters of the core layer and the shell layer, so that the repair material located at different spatial positions of the wound can set targeted release strategies and release rates based on different action stages to ensure the applicability for wound repair activity induction and efficiency improvement. That is, based on polycaprolactone and ε-polylysine, a drug diffusion sustained-release carrier for autologous platelet-rich plasma is formed, which reduces the sudden release of drugs, uniformly loads drugs, and controllable release, ensuring that the drugs in the wound area can continue to take effect and accelerate the healing process.

[0014] Preferably, the diameter of the nanofibers is 0.2 to 1.2 μm, preferably 0.4 to 1.0 μm, and more preferably 0.6 to 0.9 μm.

[0015] Preferably, the diameter of the nanofiber core layer is 0.1-1.0 μm, preferably 0.3-0.8 μm, and more preferably 0.4-0.7 μm.

[0016] Preferably, the shell thickness of the nanofiber is 0.01 to 0.5 μm, preferably 0.1 to 0.3 μm.

[0017] Preferably, the shell layer of the nanofiber is configured as a porous structure, and the fiber pore size of the shell layer is 4 to 10 nm, preferably 6 to 8 nm.

[0018] Preferably, the water contact angle of the shell layer of the nanofiber is 40 to 80 degrees, preferably 50 to 70 degrees.

[0019] Through experimental observation of the microstructure of the repair material nanofibers, the overall size, core layer size and shell layer size of the above nanofibers are optimized to give the nanofibers good mechanical properties, so that the morphology of the nanofibers has a similar structure to the extracellular matrix, which can provide structural support and mechanical strength for the tissue, and ensure that the nanofiber membrane and nanofiber three-dimensional structure prepared by the nanofibers have excellent mechanical properties and physicochemical properties. The shell layer of the nanofibers is configured as a porous structure, and the fiber pore size of the shell layer blocks the entry of bacteria while allowing active substances and growth factors to be continuously and slowly released from the core layer, thereby ensuring that the active substances and growth factors on the wound surface have a higher concentration to promote tissue healing.

[0020] The present invention also provides a method for preparing a repair material, comprising the following steps:

[0021] a. mixing polycaprolactone and ε-polylysine in medical acetone to prepare a shell solution for preparing a nanofiber shell;

[0022] b. dissolving the self-derived platelet-rich plasma in a polyvinyl alcohol solution to prepare a core layer solution for preparing the core layer of the nanofibers;

[0023] c. The shell layer solution and the core layer solution are prepared into nanofibers with a core-shell structure based on coaxial electrospinning, and the nanofibers are configured as a repair material having at least one of a one-dimensional structure to a three-dimensional structure based on at least in-situ deposition.

[0024] Electrospinning is one of the simplest and most efficient methods for preparing nanofibers. Compared with traditional nanomaterial preparation technology, electrospinning has the advantages of simple processing equipment, wide source of raw materials, low spinning cost, and scalable preparation. The micro-nano fibers prepared by electrospinning technology have high specific surface area, large length / diameter ratio and unique physical and chemical properties, and show great application potential in the fields of biological tissue engineering, wound dressings, filtration protection, drug sustained release, flexible devices, etc. The nanofibers prepared by electrospinning technology have good biocompatibility, mechanical properties and degradability and are widely used in biomedicine. The morphology of nanofibers has a similar structure to the extracellular matrix, which can provide structural support and mechanical force for tissues and provide a certain space for cell attachment and infiltration. The repair material of this application is prepared based on coaxial electrospinning technology, so that the repair material characteristics can obtain corresponding functional structures, which is of great significance for the treatment of burns and scalds.

[0025] Preferably, in step a, the mass ratio of polycaprolactone, ε-polylysine and medical acetone is (3-50):(1-5):(10-300), preferably (5-30):(1-3):(20-200); the mixing is carried out in a stirrer for 10 to 15 hours.

[0026] Preferably, in step b, the mass concentration of the polyvinyl alcohol solution is 1% to 30%, preferably 3% to 15%; the mass ratio of the polyvinyl alcohol solution to the autologous platelet-rich plasma is (1 to 5): (1 to 20), preferably (1 to 3): (1 to 10).

[0027] Preferably, in step c, the spinning voltage of coaxial electrospinning is 8-25 kV, preferably 10-20 kV; the shell solution flow rate and the core solution flow rate of coaxial electrospinning are 0.3-0.8 ml / h and 0.8-2.0 ml / h, respectively, preferably 0.4-0.6 ml / h and 1.0-1.5 ml / h; the distance between the needle tip and the receiving electrode of coaxial electrospinning is 8-25 cm, preferably 10-18 cm; the spinning nozzle diameter of coaxial electrospinning is 0.2-1.0 mm, preferably 0.3-0.6 mm. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a microstructure diagram of a repair material according to a preferred embodiment of the present invention;

[0029] Figure 2 is a performance parameter diagram of a repair material according to a preferred embodiment of the present invention;

[0030] Figure 3 This is a comparison chart of antibacterial experiments of repair materials according to a preferred embodiment of the present invention;

[0031] Figure 4 This is a comparison chart of a cell proliferation experiment of a repair material according to a preferred embodiment of the present invention;

[0032] Figure 5 This is a cell proliferation experimental analysis diagram of a repair material according to a preferred embodiment of the present invention;

[0033] Figure 6 This is a comparison diagram of wounds in living animal experiments of a repair material according to a preferred embodiment of the present invention;

[0034] Figure 7 This is a comparison diagram of wound tissue stained with HE in a histological experiment of a repair material according to a preferred embodiment of the present invention;

[0035] Figure 8 This is a Masson-stained wound tissue comparison diagram of a repair material tissue experiment according to a preferred embodiment of the present invention. DETAILED DESCRIPTION

[0036] The present invention is described in detail below with reference to the accompanying drawings.

[0037] The present application proposes a repair material, and in particular, relates to a repair material based on nanofibers, and in particular, relates to an in-situ autologous bionic repair material, which is suitable for wound repair treatment. The skin covers the whole body and becomes an important barrier to protect the internal structure of the human body and maintain the internal environment, and can protect the internal tissues of the human body from the harm of bacteria. However, the skin is susceptible to trauma. At present, skin trauma is mainly divided into acute trauma and burns. Wounds caused by surgery, trauma and superficial burns need to be bandaged with dressings to prevent bacterial invasion, avoid wound inflammation and accelerate the wound healing process. In order to improve the antibacterial ability of the dressing and the ability to load active substances and drug ingredients to improve the recovery rate and recovery quality of the wound, a nanofiber membrane for wound dressing is proposed in the prior art, and its intrinsic characteristics include high specific surface area, high porosity and a structure similar to the extracellular matrix of the skin. It can isolate bacteria based on structural characteristics and can be used to carry active substances and drug ingredients, so that the nanofiber membrane has broad prospects in the application field of wound dressings. The following is a specific description of the repair material of the present invention, its preparation process and performance experimental verification process.

[0038] Example 1

[0039] Regarding the preparation method of the repair material, in this embodiment, a coaxial electrospinning method is used to prepare the repair material composed of core-shell structure nanofibers in this application. The coaxial electrospinning method needs to configure the shell solution and the core solution of the core-shell structure of the repair material nanofiber as the shell raw material and the core raw material. The main active substances of the shell solution are polycaprolactone and ε-polylysine, and medical acetone is used as a solvent and the solution is evenly mixed; the main active substance of the core solution is autologous platelet-rich plasma, and polyvinyl alcohol solution is used as a solvent. A coaxial electrospinning method is used to prepare nanofibers with a core-shell structure, and the nanofibers are processed into a repair material. The processing of the nanofibers into a repair material is carried out in a manner that the repair material is formed based on the nanofiber parameter setting to include at least one of a one-dimensional structure to a three-dimensional structure. For example, a one-dimensional structure includes different nanofiber segments on one dimension, a two-dimensional structure includes different nanofiber partitions on a two-dimensional plane, and a three-dimensional structure includes different nanofiber stratifications in a three-dimensional solid. Specifically, 2 g of polycaprolactone (PCL) and 0.4 g of ε-polylysine (ε-PL) were dissolved in 10 g of medical acetone and stirred in a magnetic stirrer for 12 hours as the shell solution for coaxial electrospinning; 0.5 g of polyvinyl alcohol was dissolved in 10 g of water to obtain a 5% polyvinyl alcohol solution (PVA), and autologous platelet-rich plasma activated by CaCl2 and passed a blood routine test was dissolved in a 5% polyvinyl alcohol solution (PVA). The mass ratio of autologous platelet-rich plasma (autologous PRP, hereinafter referred to as PRP) to polyvinyl alcohol solution (PVA) was 2:1, which was used as the core solution for coaxial electrospinning.

[0040] In order to obtain targeted comparative experimental results, this embodiment is based on the different active substances polycaprolactone, ε-polylysine, autologous platelet-rich plasma and different coaxial electrospinning schemes. Multiple groups of nanofiber repair materials are set up, and the repair materials are prepared as nanofiber membranes based on nanofibers. The coaxial electrospinning scheme includes traditional electrospinning and in-situ electrospinning. Traditional electrospinning is to process the nanofiber membrane prepared by the electrospinning device and cover the wound to form a nanofiber membrane similar to gauze; in-situ electrospinning is based on the coaxial electrospinning device to directly deposit the prepared nanofibers as repair materials in situ on the wound and directly form a nanofiber membrane that fully covers the wound.

[0041] Specifically, three groups of nanofiber membranes, PCL, PCL+ε-PL, and PCL+PRP+ε-PL, were prepared by traditional electrospinning. The electrospinning voltage of the above three groups was 17.6KV, and the flow rates of the electrospinning core layer solution and the shell layer solution were 0.5ml / h and 1.2ml / h, respectively. The distance between the electrospinning needle and the receiving electrode was about 15cm, and all spinning processes were carried out at 25°C and 50% humidity. In-situ PCL+PRP+ε-PL (In-situPCL+PRP+ε-PL) group nanofiber membranes were prepared by in-situ electrospinning and based on the preparation method of this application. In step a, the mass ratio of polycaprolactone, ε-polylysine and medical acetone was 5:1:25, and the mixing was mixed by a mixer for 12 hours. In step b, the mass concentration of the polyvinyl alcohol solution was 5%; the mass ratio of the polyvinyl alcohol solution to the self-sourced PRP was 1:2. In step c, the spinning voltage of coaxial electrospinning is 10kv; the flow rates of the shell solution and the core solution of coaxial electrospinning are 0.5ml / h and 1.2ml / h respectively; the distance between the needle and the receiving electrode of coaxial electrospinning is 10cm; the diameter of the spinning nozzle of coaxial electrospinning is 0.4mm.

[0042] The above four groups of repair materials, namely PCL, PCL+ε-PL, PCL+PRP+ε-PL group nanofiber membrane and In-situ PCL+PRP+ε-PL group nanofiber membrane, can obtain targeted comparative analysis results based on experiments to clarify the contribution of the active substances and the electrospinning scheme to the repair materials.

[0043] Regarding the microstructure of the nanofiber membrane prepared by the In-situ PCL+PRP+ε-PL group, Figure 1 a is a SEM image of the nanofibers of the present application. The diameter of the nanofibers ranges from 0.2 to 1.2 μm, most of the diameters are between 0.4 and 1.0 μm, the median and the average are between 0.6 and 0.9 μm, and the average diameter of the nanofibers is about 0.7 μm. Figure 1 b is a TEM image of the nanofibers, from which it can be seen that the nanofibers are coaxial structures, that is, the nanofibers of the repair material of the present application have coaxial core-shell structures. The nanofibers are further dyed, and the solutions corresponding to the core layer and the shell layer are labeled with calcein and rhodamine B, respectively. Figure 1ce is under a confocal microscope, with 495nm wavelength excitation, the core layer can be seen to be green, and with 540nm wavelength excitation, the shell layer can be seen to be red, confirming the core-shell structure of the nanofiber and the PRP is concentrated in the core layer. Corresponding to the size ratio of the core layer diameter of the nanofiber to the diameter of the nanofiber, the diameter of the nanofiber core layer is 0.1 to 1.0μm, preferably 0.3 to 0.8μm, more preferably 0.4 to 0.7μm; and the thickness of the nanofiber shell layer is 0.01 to 0.5μm, preferably 0.1 to 0.3μm. That is, the core layer of the nanofiber is located on the inside and the shell layer coaxially wraps the core layer on the outside to form a nanofiber with a coaxial core-shell structure. The core layer is used to provide growth factors, the shell layer allows growth factors to pass through and release to act on wound tissue, the first component in the shell layer as the main body of the shell layer is polycaprolactone, and the second component in the shell layer used to modify the first component is ε-PL, and the effect of ε-PL on PCL at least includes the improvement of wettability and the improvement of antibacterial ability. The third component of the core layer is PRP. In the traditional single-needle electrospinning process, PRP will directly mix and contact with organic solvents, resulting in inactivation and denaturation of biological proteins and cytokines in PRP. The core-shell structure is designed to allow PRP to be spun with aqueous solvents inside the nanofibers and the outer shell of the fiber to be spun with organic solvents, which can well protect the activity of PRP biological proteins and cytokines. In addition, compared with traditional single-needle electrospinning, the coaxial electrospinning method for preparing core-shell structures can usually slow down the release rate of doped substances in the fiber based on the porous structure of the nanofiber shell layer, such as growth factors, drugs, etc. The slow and continuous release can usually meet the drug concentration requirements for tissue repair.

[0044] Figure 2 a is the FTIR spectrum of the in-situ PCL+PRP+ε-PL nanofiber membrane. The nanofiber (green line) is at 1725 cm -1 There is a carboxyl stretching vibration peak of the ester group at 1245 cm -1 There are stretching vibration peaks of -COC- at 1640cm -1 and 1520cm -1 The vibration peak at comes from ε-PL (red line), which proves that the main body of the nanofiber is composed of PCL and ε-PL. Since PRP is rich in growth factors and distributed inside the core layer of the nanofiber, in order to make it easier to release drugs and active substances in the core layer of the nanofiber, the nanofiber should have a porous structure and good wettability, so that the drugs and active substances can diffuse out in time after the tissue fluid infiltrates the nanofiber. First, the N2 adsorption-desorption curve of the nanofiber was tested. Figure 2As can be seen in b, there is an obvious hysteresis loop between the adsorption and desorption curves, which indicates that the nanofibers are porous structures with a fiber pore size of 4 to 10 nm, preferably 6 to 8 nm. Second, the contact angle of water was tested. Figure 2 c It can be seen that the water contact angle of the PCL group is about 109°, which is a hydrophobic material. After adding ε-PL, the water contact angle changed from 109° to about 62°. Based on the different proportions of the active components, the water contact angle can be controlled at 40 to 80 degrees, preferably 50 to 70 degrees, which successfully changed the hydrophilicity of the nanofiber membrane. The nanofiber membrane has good hydrophilicity and can form a moist microenvironment on the wound surface, effectively absorb the exudate from the wound, and is conducive to wound repair. Third, the release curves of several growth factors that play a positive role in burns and scalds were evaluated. Figure 2 It can be seen that PDGF-BB is released faster than TGF-β and VEGF in tissue fluid, which may be due to the fact that PDGF-BB is more water-soluble, while TGF-β and VEGF are more fat-soluble. In addition, it can be seen that the content of PDGF-BB is higher than that of TGF-β and VEGF. Considering that the content of these three growth factors varies for different people, the specific content ratio of autologous growth factors is the best content ratio for this person and effectively reduces rejection, which is why this application uses autologous PRP.

[0045] Based on the experimental results of microstructure and spectral analysis, the nanofibers prepared by the in-situ coaxial electrospinning method of the present application have a core-shell structure, and the first component of the shell layer is polycaprolactone, which can form a nanofiber shell layer with a fiber pore size based on electrospinning. When the nanofibers made of polycaprolactone cover the wound, the size of the fiber pore size is smaller than the size of the bacteria, thereby blocking the invasion of bacteria into the wound, but polycaprolactone is a hydrophobic material, making it difficult for wound tissue to adhere. The second component of the shell layer is ε-polylysine, which is used to modify polycaprolactone, at least including improving the antibacterial and wettability of polycaprolactone. As can be seen from the above experimental data, the improvement in wettability is reflected in that ε-polylysine can greatly reduce the water contact angle of polycaprolactone, so that the wound tissue can be effectively attached, which is conducive to cell adhesion and proliferation. Moreover, the preparation parameters in the preparation method of the present application are also the optimized design implementation parameters and preferred implementation scheme for producing the nanofibers of the repair material of the present application formed based on experimental design and debugging. The selection of preparation parameters determines the range of material parameters such as nanofiber diameter, core layer diameter, shell layer thickness, shell layer fiber pore size and water contact angle. The range of the above material parameters determines the antibacterial properties, wettability and growth factor release and distribution of the repair material of the present application. That is, the realization of the technical effect of the repair material of the present application is closely related to the material parameters and preparation parameters in the present application, so that the nanofiber repair material with a core-shell structure prepared based on the preparation method of the present application can be suitable for wound repair and have excellent antibacterial and healing properties.

[0046] Example 2

[0047] Comparative analysis of the antibacterial properties of repair materials: To compare the antibacterial properties of three groups of nanofiber membranes, PCL, PCL+ε-PL, PCL+PRP+ε-PL, and In-situ PCL+PRP+ε-PL, prepared by conventional electrospinning equipment. The antibacterial effect was evaluated by the disk agar diffusion method. First, in a sterile environment, approximately 1×10 8 The suspension of Escherichia coli and Staphylococcus aureus with 10 cells was inoculated on a ready-to-use nutrient agar medium (9cm×9cm). Several groups of nanofiber membranes used in the experiment were cut into nanofiber mats with a radius of 1cm. The nanofiber mats were then placed in the center of the 9cm×9cm agar medium coated with bacteria and cultured in a constant temperature and pressure box at 30℃ for 18 hours. Since burn wounds are extremely susceptible to bacterial infection, if nanofibers can kill Gram-negative and Gram-positive bacteria, it can be beneficial to the treatment of burns. Therefore, the in vitro antibacterial evaluation was carried out by the disk agar diffusion method. Figure 3The control group in a is untreated Escherichia coli and Staphylococcus aureus. No antibacterial ring appeared after covering the PCL fiber, indicating that PCL has no killing effect on bacteria. The other three groups, including PCL+ε-PL, PCL+PRP+ε-PL, and In-situ PCL+PRP+ε-PL, all showed very obvious antibacterial rings with basically the same radius, indicating that the antibacterial effect should come from ε-PL. ε-PL can interfere with the normal synthesis of microbial cell walls, reduce the ability of bacteria to resist osmotic pressure, and cause the bacteria to deform, rupture, and die. From further SEM images of Escherichia coli and Staphylococcus aureus ( Figure 3 b, d) It can be confirmed that the untreated E. coli has a rod-shaped structure, a smooth surface and a full shape without cell damage ( Figure 3 b). After being treated with PCL+PRP+ε-PL nanofibers, the bacterial cell membrane shrank and there was no plumpness, and constriction appeared on the cell membrane surface ( Figure 3 c). Staphylococcus aureus and Escherichia coli showed similar results ( Figure 3 d, e). This can confirm that after the addition of ε-PL, it can destroy the cell membrane structure of microorganisms, leading to bacterial lysis and thus achieving a bactericidal effect.

[0048] Comparative analysis of cytotoxicity of repair materials: Since the nanofiber membrane containing PRP is ultimately used in the human body, it is required to be non-toxic. Therefore, fibroblasts were inoculated on 4 different groups and a control group glass slide to detect their cell responses. After the nanofiber membrane was disinfected with alcohol and irradiated with ultraviolet light, CCK-8 was used to determine the cell metabolic activity. All experimental steps need to be performed under a sterile clean bench. This experiment is divided into the above 5 groups, including the traditional electrospinning group PCL, PCL+ε-PL group, PCL+PRP+ε-PL group and In-situ PCL+ε-PL+PRP group. There are 4 replicates in each group. The above 5 groups of nanofiber membranes and the empty glass slides of the control group were placed in a 24-well plate, washed once with phosphate buffer solution (PBS), washed three times with serum-free medium, and then added with 100μl of complete medium and placed in a 37-degree constant temperature incubator. Next, the fibroblasts with a confluence of 90% were taken out of the incubator, rinsed with phosphate buffered saline (PBS) three times, and then placed in the incubator after adding 200 μl of trypsin to digest the cells. After 3 minutes, the cells were taken out and digested with 1 ml of complete culture medium (DMEM high glucose hyclone, 10% fetal bovine serum, 1% double antibody). After repeatedly blowing the cells off, they were placed in a 1.5 ml EP tube and centrifuged (900 rpm, 5 min). The supernatant was discarded and the cells were resuspended in 1 ml of complete culture medium. 10 μl of the cell suspension was extracted for counting, and the number of cells obtained was 80×10 4 / ml. The number of cells planted in each well is about 10 5 / ml, after preparing the required cell suspension, pipette 100μl of cell suspension and plant it in each space. After 2 hours, fill the culture medium to 700μl. Measure the number of cell proliferation after 4 hours, 12 hours, 1, 3, and 5 days respectively. After removing the old culture medium, rinse once with phosphate buffer solution (PBS), and add complete culture medium containing 10% CCK-8 reagent (400μl per well). Note that it is necessary to avoid light when adding liquid. Incubate at 37 degrees in a humidified atmosphere of 5% CO2 for 2h. Add 100μL of the liquid in the 2-well plate to the 96-well plate, 3 replicates per group, wrap with tin foil, and monitor the absorbance at 450nm with an enzyme reader.

[0049] Due to further in vivo applications, nanofibers containing PRP are required to be non-cytotoxic. Therefore, human fibroblasts were seeded on the nanofiber membranes to evaluate their cellular response. Polystyrene tissue culture plates (TCP) were incubated with fibroblasts on the same day as a control group. The attachment and morphology of human fibroblasts were determined by double-labeled fluorescent staining of the actin cytoskeleton and the nucleus. Figure 4 ae show cells on different groups of nanofiber membranes. Figure 5 The proliferation of human foreskin fibroblasts (HSFs) after 1, 3, and 5 days of culture on the control group, PCL, PCL+ε-PL, PCL+ε-PL+PRP, and In-situ PCL+ε-PL+PRP was shown. The control group was a positive control group, and each group showed an upward trend from the first day to the fifth day. The PCL group showed more significant proliferation than the control group, which shows that the fiber spun from pure PCL itself has good biocompatibility. After HSFs were cultured on different samples for 1 day, the proliferation effect of HSFs on different samples was not obvious. After the third day of culture, the proliferation of HSFs on PCL+ε-PL was better than that on PCL. It shows that although ε-PL is an antibacterial substance, it has no toxic effect on cells. After HSFs were cultured on different samples for 5 days, the proliferation of HSFs on PCL+ε-PL+PRP and In-situ PCL+ε-PL+PRP was significantly better (P<0.01) than that on PCL and PCL+ε-PL groups. These experimental results show that PRP promotes the proliferation of HSFs, and these nanofibers are non-toxic and have no side effects on cells.

[0050] Comparative analysis of in vivo experiments on repair materials: In order to test the efficacy, 40 SD rats were randomly divided into 5 groups. According to the shape of the skin burn wound, PCL, PCL+ε-PL, and PCL+ε-PL+PRP fiber scaffolds of appropriate shapes were cut respectively. In the In-situPCL+PRP+ε-PL group, the PCL+PRP+ε-PL nanofiber membrane was directly deposited on the wound surface using a handheld electrospinning device to cover the wound on the back of the rat skin. The wounds of each group were covered with gauze and fixed with silk sutures. To avoid mutual interference between animals, they were kept in single cages. After the wounds of the burned rats were covered with scaffolds or naturally healed, they were photographed and the healing status was observed on days 1, 3, 5, 7, 9, 14, and 21. The recovery of deep second-degree burns was evaluated using SD rats, and the recovery status was recorded on days 3, 5, 7, 9, 11, 14, and 21. Second-degree burns affect the upper and deeper layers of the dermis and are white or yellow in color, with blisters and a moist appearance. Figure 6 As shown in a, 3 days after the scald, the wound swelling and periwound redness in the control group were the most obvious, followed by the PCL group. This is because the PCL nanofiber membrane can prevent airborne bacteria from infecting the wound and protect the wound. On the 5th day after the scald, the recovery effect of the PCL+ε-PL group was significantly better than that of the PCL group. This is attributed to the antibacterial ability of ε-PL, which reduces bacterial infection and is beneficial to wound recovery. On the 14th day, obvious scabs can still be seen in the PCL+ε-PL group. In sharp contrast, the wound scabs in the PCL+ε-PL+PRP group have completely disappeared and almost completely recovered on the 21st day. This shows that the various growth factors contained in PRP are of great help to wound healing and can effectively promote wound repair.

[0051] The nanofiber membrane obtained by traditional electrospinning is a two-step process of spinning and using. The nanofiber membrane is cut and then covered on the wound surface. However, the nanofiber membrane obtained by this traditional method is similar to the use of gauze and has poor adhesion to the wound. Figure 6 c is to cover the skin with a traditional nanofiber membrane. The adhesion between the nanofiber membrane and the skin was tested to be 0.02N. Different from this, the handheld device based on uses an in-situ spinning method to directly deposit the fibers onto the skin. The adhesion between the nanofiber membrane and the skin was tested to be 0.18N. Better fit will have a positive effect on repair. Therefore, based on the PCL+ε-PL+PRP group, the difference between the traditional method and the in-situ spinning method for burn and scald repair was further compared. Figure 6As can be seen in b, the In-situ PCL+PRP+ε-PL group showed a faster recovery speed than the traditional spinning group. This may be due to better fit, which can effectively prevent external bacteria from invading the wound through the fit gap of the nanofiber membrane-skin interface, thereby accelerating the recovery of burns. This shows that the in-situ deposition method can further improve the effect of dressings containing antibacterial and growth factors. Better fit not only reduces the gap and reduces the probability of bacterial infection, but also reduces the distance from the skin, which is conducive to the timely and effective delivery of growth factors to the wound, while improving the efficacy of antibacterial and growth factors.

[0052] Comparative analysis of tissue response to repair materials: Histological analysis was performed, and the new tissue was frozen and sectioned, and then HE staining, Masson staining and other methods were used to observe the healing process of rat skin wounds (wound inflammation, fibroblast proliferation, collagen secretion and typing, epidermal differentiation, etc.). The scalded tissues of SD rats on the 1st, 7th, 14th and 21st days were fixed on slides for hematoxylin-Yinhong (H&E) and Masson staining. HE and Masson staining were used to evaluate the number of bacteria around the wound and the progress of wound recovery, respectively. The histopathological changes of the wound were observed under a microscope.

[0053] Wound repair of burns is a very complex process. In order to analyze the relationship between wound infection and recovery from a microscopic perspective, HE staining was performed on the samples ( Figure 7 ) to evaluate the state of wound repair. From the 3rd to the 7th day after the burn, it can be seen that there are many lymphocytes in the control group, and relatively few in the PCL group. This shows that the PCL group has fewer lymphocytes because the coverage of the nanofiber membrane can protect the wound from bacterial invasion. On the 7th day, the PCL+ε-PL group showed fewer lymphocytes than the PCL group. This is because ε-PL has antibacterial properties and can lyse bacteria to reduce bacteria in the wound. On the 14th day, the PCL+ε-PL+PRP group had significantly more blood vessels than the PCL+ε-PL group. This is because PRP contains a variety of growth factors. When PRP encounters tissue fluid, the Ca2+ in the tissue fluid activates PRP to release growth factors and accelerate tissue repair and regeneration. On the 21st day, the In-situ PCL+ε-PL+PRP group showed more blood vessels and fewer neutrophils than the PCL+ε-PL+PRP group. This is because the fibers deposited in situ on the wound have better adhesion, which can effectively prevent external bacteria from invading the wound through the gap between the nanofiber membrane and the skin interface to improve antibacterial properties. It also reduces the gap distance between the skin and is conducive to the timely and effective delivery of growth factors to the wound, while improving the repair effect of growth factors on tissues. This confirms from a microscopic perspective that the in situ deposition method can further enhance the effect of dressings containing antibacterial and growth factors. Further analysis by Masson's trichrome staining ( Figure 8 ) Observe the collagen deposition in the wound tissue. It can be seen that on the 3rd day, only a small amount of collagen fibers appeared in all groups. On the 7th day, the collagen fibers of all wound groups were irregularly arranged. On the 14th day, there were fewer blue collagen fibers and granulation tissue in the PCL+ε-PL group, while the collagen fibers in the PCL+ε-PL+PRP group and the In-situ PCL+PRP+ε-PL group were relatively dense. On the 21st day, the In-situ PCL+ε-PL+PRP group was the first to form a complete layer of epithelial tissue on the surface of the wound tissue, indicating that tissue repair had been completed. These experimental results show that it is far from enough to rely solely on antibacterial agents to achieve the purpose of wound healing. Wound repair not only requires bactericidal effects to ablate bacteria and reduce inflammation, but also promotes wound healing through the joint action of multiple growth factors. The in situ deposition method can further enhance the effect of dressings containing antibacterial and growth factors.

[0054] Based on the above-mentioned antibacterial / cytotoxicity / in vivo experiment / tissue examination and other performance comparison experiments, it can be known that the technical effect of the repair material of the present application is closely related to the active substances such as ε-polylysine, autologous platelet-rich plasma and material parameters. For example, for ε-polylysine, ε-polylysine not only improves the wettability of the polycaprolactone in the shell of the repair material and enhances the antibacterial properties, but the shell structure formed by ε-polylysine and polycaprolactone is of great significance to the release rate and distribution of growth factors in autologous platelet-rich plasma. The shell of the repair material formed based on ε-polylysine and polycaprolactone coaxially wraps the autologous platelet-rich plasma located in the core layer and has fiber pores that allow growth factors in the autologous platelet-rich plasma to pass through. Wound tissue cells adhere and multiply on the outer surface of the shell, and growth factors move from the inside of the shell to the outside of the shell to maintain the growth factors near the tissue cells at a higher concentration, so that the shell acts as an organic degradable barrier to isolate the wound environment and autologous platelet-rich plasma, thereby preventing the autologous platelet-rich plasma from being decomposed by enzymes on the wound surface and being unable to continuously release growth factors. The fiber pore size of the shell layer matches the size of the growth factor, and the degradation rate of the shell layer is also adapted to the life cycle of the growth factor released by the autologous platelet-rich plasma, so that the autologous platelet-rich plasma located in the core layer can continuously and stably release the growth factor to maintain a high concentration of tissue cell growth factor, that is, the shell layer of the repair material formed by ε-polylysine and polycaprolactone in the present application and the core layer of the repair material formed by the autologous platelet-rich plasma have a specific correlation in terms of microstructural parameters and action mechanism, and this specific correlation is achieved based on the matching of the fiber pore size of the shell layer with the size of the growth factor and the adaptation of the degradation rate of the shell layer to the life cycle of the growth factor released by the autologous platelet-rich plasma.

[0055] In summary, the repair material of the present application has excellent antibacterial properties when used in combination with polycaprolactone and ε-polylysine, and can improve the wettability of polycaprolactone, so that the wound tissue cells can show good biocompatibility with the shell layer of the repair material, which is beneficial to cell adhesion and proliferation. This also provides an active inducing environment for the consistent effect of the growth factors released from the core layer of the repair material, and the autogenous PRP in the core layer can also slowly and continuously release growth factors. This autogenous PRP perfectly matches the patient's wound environment without allergic reactions, and the content ratio of each growth factor meets the requirements of the wound environment, which can effectively ensure the targetedness and applicability of the growth factors for the activity induction of wound tissue cells.

[0056] Example 3

[0057] The dressing of this embodiment is constructed by forming a core-shell structure of nanofibers based on a coaxially arranged core layer and a shell layer, wherein the shell layer of the nanofiber contains at least polycaprolactone for forming the shell body and ε-polylysine and zeolite imidazolate skeleton material (ZIF-8) for modifying the polycaprolactone, and the core layer of the nanofiber contains at least autologous platelet-rich plasma for releasing growth factors.

[0058] Preferably, the zeolite imidazolate framework material is arranged in the shell of the nanofiber in a manner of coating or embedding in polycaprolactone modified by ε-polylysine. The particle size range of the zeolite imidazolate framework material is determined according to the zeolite imidazolate framework material being able to increase the diffusion release rate of the growth factor through the nanofiber shell without causing the wound tissue environment to extend to the inner side of the nanofiber shell. For example, the particle size range of the zeolite imidazolate framework material (ZIF-8) is 5 to 30 nm, preferably 7 to 15 nm. The zeolite imidazolate framework material of the above particle size range can be used to increase the infiltration area of ​​the nanofiber and increase the diffusion release rate of the growth factor from the inner side to the outer side of the nanofiber. If the particle size of the zeolite imidazolate skeleton material is too small, the quality of the growth factor diffusion channel cannot be improved, which is not conducive to the improvement of the growth factor diffusion release rate; if the particle size of the zeolite imidazolate skeleton material is too small, it will affect the mechanical properties of the nanofiber membrane, and the tissue fluid and biological enzymes retained on the outside of the nanofiber shell based on the hydrophilic adhesion of the nanofibers may act on the autologous platelet-rich plasma on the inside along the channel formed by the zeolite imidazolate skeleton material, thereby causing adverse consequences for the diffusion release of growth factors and offsetting the beneficial effects brought about by the increase in the growth factor diffusion release rate.

[0059] Preferably, the shell of the nanofiber also contains poly(glycidyl alcohol) (PGL), which is evenly arranged in the shell in a manner that can adjust the processability of the nanofiber shell and control the degradation rate in vivo and in vitro. Polycaprolactone (PCL) and its monomers are non-toxic and have good biocompatibility and biodegradability. PCL has good permeability to small molecule drugs and can be used as a drug diffusion-type sustained-release carrier for dissolution, while PGL-PCL (poly(glycidyl alcohol)-polycaprolactone) can improve processability and control the degradation rate in vivo and in vitro, so that the drug diffusion-type sustained-release carrier can be set differently based on different repair positions and different repair cycles at the same position.

[0060] This embodiment further improves the nanofiber dressing to enhance the antibacterial properties and tissue adhesion of the dressing and improve the drug diffusion and sustained release properties. For the above-mentioned nanofiber dressing prepared by polycaprolactone, ε-polylysine and autologous platelet-rich plasma, the autologous platelet-rich plasma rich in growth factors is distributed inside the nanofiber core layer, so that the growth factor needs to use the nanofiber shell composed of polycaprolactone and ε-polylysine as a drug diffusion and sustained release carrier, so that the growth factor inside the nanofiber shell can be stably and continuously diffused and released to the outside of the nanofiber shell. In order to improve the diffusion range and release rate of the growth factor in the nanofiber core layer, the fiber pore size of the nanofiber shell should be suitable for autologous platelet-rich plasma and the nanofiber has good infiltration; in order to promote the interaction between growth factors and wound tissue to increase the wound healing rate, the nanofiber should have a large infiltration area to increase the space for the adhesion and proliferation of wound tissue cells, so that the nanofiber can also increase the efficiency of the growth factor and wound tissue based on the increase in the infiltration area.

[0061] like Figure 2 As shown in Figure d, the growth factors released by autologous platelet-rich plasma to promote tissue repair are mainly platelet-derived growth factor PDGF-BB, transforming growth factor TGF-β and vascular endothelial growth factor VEGF. Among them, platelet-derived growth factor PDGF-BB has the effects of promoting mitosis, differentiation, chemotaxis and angiogenesis, and transforming growth factor TGF-β is used to regulate cell growth and differentiation; vascular endothelial growth factor VEG is highly specific to vascular endothelial cells and has important biological functions such as promoting vascular permeability and promoting the proliferation of endothelial cells. According to Figure 2From the cumulative release curves of different growth factors in d, it can be seen that the different growth factors released by autologous platelet-rich plasma are diffused from the nanofiber shell to the outside of the nanofiber shell and present a curve of content change over time in the tissue fluid. Since PDGF-BB tends to be water-soluble, while TGF-β and VEGF tend to be fat-soluble, the release rate of PDGF-BB in the tissue fluid is faster than that of TGF-β and VEGF; and the content of PDGF-BB is higher than that of TGF-β and VEGF. The content difference and specific content ratio are determined by the autologous platelet-rich plasma from the patient himself, and its specific ratio is the best ratio for the patient and can effectively avoid rejection. However, for drug diffusion and sustained release carriers based on polycaprolactone and ε-polylysine, it takes a long time for growth factors to reach a stable high content or high concentration. For example, the time for PDGF-BB, TGF-β and VEGF to reach 80% of the maximum concentration is 15 days, 10 days and 10 days respectively, that is, in the early stage of wound healing when the demand for growth factors is the largest, the drug diffusion and sustained release carrier based on polycaprolactone and ε-polylysine has a slow diffusion release rate for growth factors and cannot provide a high concentration of growth factors in the early stage of healing. Therefore, it is considered to improve the nanofiber shell to improve the release rate of growth factors and the efficiency of promoting healing of drug diffusion and sustained release carriers based on polycaprolactone and ε-polylysine.

[0062] Metal-organic frameworks (MOFS) are porous, crystalline materials formed by the self-assembly of metal ions or metal clusters and multi-dentate organic ligands. This inorganic-organic hybrid material has the excellent properties of both inorganic and organic materials. It not only has a high specific surface area, adjustable size and porosity, but also has a high drug loading rate and is easy to modify the surface. Therefore, it is widely used in catalysis, gas capture, sensors, drug delivery and other fields. Zeolite imidazolate framework material (ZIF-8) is a type of metal-organic framework formed by the coordination of zinc ions (Zn2+) and 2-methylimidazole (2-MiM). It exhibits good biocompatibility and acidic environment sensitivity. It remains stable under physiological conditions and disintegrates under acidic conditions. It is an ideal carrier for drug transport and sustained release. The size of nanomaterials is crucial to their performance. A small change in size can have a decisive impact on the performance of the material. Therefore, the particle size control of ZIF-8 and the functional size composite regulation of ZIF-8 and other materials are of great significance for the application of ZIF-8 and its composite materials in the process of biomolecule transport. The preparation methods of ZIF-8 include solvent thermal synthesis, microwave-assisted method and microfluidic synthesis. The particle size control methods include adjustment of reaction parameters, surfactant adjustment and participation of crystallization regulator. ZIF-8 with a particle size range of 10nm-1μm can be prepared.

[0063] Therefore, ZIF-8 in a selected particle size range is added to the shell solution and mixed evenly and prepared as the shell of the nanofiber based on coaxial electrospinning, so that the ZIF-8-coated or embedded PCL-ε-PL nanofibers show a large specific surface area, thereby increasing the drug loading of the nanofibers from 15% to 25%. ZIF-8 can also increase the number and quality of channels for the diffusion and release of growth factors from the inner side of the nanofiber shell to the outer side of the shell based on the particle size selection in a specific range. ZIF-8-coated or embedded PCL-ε-PL nanofibers also significantly increase the infiltration area and adhesion space of tissue cells in the nanofiber shell, thereby enhancing the interaction between growth factors and wound tissue. Antibacterial experiments found that ZIF-8 and ε-PL exhibit dual antibacterial properties. ε-PL, as a polypeptide, is loaded on ZIF-8 to further kill residual bacteria, so that the dressing prepared by this PCL-ZIF-8-εPL nanofiber can improve the barrier ability for external bacteria and the killing effect on internal bacteria, and can prevent external bacteria from infecting the wound and show efficient bactericidal properties. The drug diffusion and sustained-release carrier based on PCL-ZIF-8-εPL nanofibers can shorten the wound healing time from 22 days to 17 days by improving antibacterial properties, increasing the infiltration area, and increasing the growth factor release rate.

[0064] It should be noted that the above specific embodiments are exemplary, and those skilled in the art can come up with various solutions inspired by the disclosure of the present invention, and these solutions also belong to the disclosure scope of the present invention and fall within the protection scope of the present invention. Those skilled in the art should understand that the present invention description and its drawings are illustrative and do not constitute a limitation of the claims. The protection scope of the present invention is defined by the claims and their equivalents.

Claims

1. A repair material, characterized in that: The repair materials include: At least the nuclear lamina for providing growth factors; a shell layer that allows at least the growth factors of the core layer to pass through and be released; The repair material is configured as a nanofiber having a core-shell structure based on the core layer and the shell layer in a manner that at least includes a coaxial arrangement. The shell layer at least comprises a first component for forming a main body of the shell layer and a second component for modifying the first component; the first component is configured as polycaprolactone, and the second component is configured as ε-polylysine, The shell layer also contains a zeolite imidazolate skeleton material, wherein the zeolite imidazolate skeleton material is arranged in the shell layer in a manner of being coated or embedded in polycaprolactone modified with ε-polylysine, and the particle size range of the zeolite imidazolate skeleton material is determined in accordance with the zeolite imidazolate skeleton material being able to enhance the diffusion release rate of growth factors through the nanofiber shell layer without causing the wound tissue environment to extend to the inner side of the nanofiber shell layer.

2. The repair material according to claim 1, characterized in that The nuclear layer includes at least a third component for releasing the growth factor.

3. The repair material according to claim 1 or 2, characterized in that: The third component is configured as autologous platelet-rich plasma.

4. The repair material according to claim 1, characterized in that The diameter of the nanofiber is 0.2-1.2 μm.

5. The repair material according to claim 1 or 2, characterized in that: The diameter of the nanofiber core layer is 0.1-1.0 μm, and the thickness of the nanofiber shell layer is 0.01-0.5 μm.

6. The repair material according to claim 1, characterized in that The shell layer of the nanofiber is configured as a porous structure, and the fiber pore size of the shell layer is 4 to 10 nm; The water contact angle of the shell layer of the nanofiber is 40 to 80 degrees.

7. A method for preparing a repair material, characterized in that: The preparation method is used to prepare the repair material according to any one of claims 1 to 6, comprising the following steps: a. mixing polycaprolactone and ε-polylysine in medical acetone to prepare a shell solution for preparing a nanofiber shell; b. dissolving the self-derived platelet-rich plasma in a polyvinyl alcohol solution to prepare a core layer solution for preparing the core layer of the nanofibers; c. The shell layer solution and the core layer solution are prepared into nanofibers with a core-shell structure based on coaxial electrospinning, and the nanofibers are configured as a repair material having at least one of a one-dimensional structure to a three-dimensional structure based on at least in-situ deposition.

8. The preparation method according to claim 7, characterized in that: In step a, The mass ratio of polycaprolactone, ε-polylysine and medical acetone is (3-50):(1-5):(10-300); The mixture is mixed using a mixer, and the mixing time is 10 to 15 hours.

9. The preparation method according to claim 7 or 8, characterized in that: In step b, The mass concentration of the polyvinyl alcohol solution is 1% to 30%; The mass ratio of the polyvinyl alcohol solution to the autologous platelet-rich plasma is (1-5): (1-20).

10. The preparation method according to claim 7, characterized in that: In step c, The spinning voltage of coaxial electrospinning is 8 to 25 kV; The flow rates of the shell solution and the core solution of coaxial electrospinning were 0.3-0.8 mL / h and 0.8-2.0 mL / h, respectively; The distance between the needle and the receiving electrode of coaxial electrospinning is 8 to 25 cm.

Citation Information

Patent Citations

  • A core-shell electrospun chitosan nanofiber wound dressing and its preparation method

    CN107137748B

  • In-situ autologous bionic repair material for fat liquefaction wound as well as preparation method and application of in-situ autologous bionic repair material

    CN108434529A

  • Method for in-situ nursing of skin with burns and scalds

    CN110101897A

  • Core-shell drug-loaded nano-fiber dressing and preparation method thereof

    CN110464866A